Human Computer Interaction - Pavlidis, Ioannis (IntechOpen, 2008)
This book includes 23 chapters introducing basic research, advanced developments and applications. The book covers topics such us modeling and practical realization of robotic control for different applications, researching of the problems of stability and robustness, automation in algorithm and program developments with application in speech signal processing and linguistic research, system's applied control, computations, and control theory application in mechanics and electronics.